Upaya Meningkatkan Kemampuan Bahasa Melalui Aktivitas Bermain Peran Pada Anak Usia Dini - Haryati, Haryati (Jurnal Ilmiah Wahana Pendidikan, 2024)
In improving children's language development skills, of course, the right method is needed to develop early childhood language. One of the methods that can be provided is the role-playing method. This study aims to find out the efforts that can be made to improve early childhood language skills. This research was conducted using a literature study research method, in this case the researcher used several relevant research sources in the form of books, articles and previous journals. The focus of this research is efforts to improve language skills through play methods in early childhood. The results of this study show that role-playing in early childhood is a very effective way to be used in the learning process in early childhood. This can be proven from several previous research results that are relevant to improving language skills through role-playing methods in early childhood.